2018
DOI: 10.3892/mmr.2018.9191
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC15 promotes colon cancer cell proliferation and metastasis by regulating the miR‑4310/LGR5/Wnt/β‑catenin signaling pathway

Abstract: Previous studies have indicated that overexpression of long noncoding RNA cancer susceptibility 15 (CASC15) may promote tumor development and progression in gastric cancer and hepatocellular carcinoma. However, the function of CASC15 in colon cancer remains unknown. In the present study, the expression of CASC15 was upregulated in colon cancer tissues and its expression was correlated with clinical Tumor‑Node‑Metastasis stage and tumor metastasis. In addition, knockdown of CASC15 significantly inhibited the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…3), thereby enhancing the proliferation and migration of NSCLC cells. In line with this, other groups have recently reported that CASC15 could promote tumorigenesis by activating Wnt//β-catenin signaling pathway in colon cancer and melanoma, suggesting that CASC15/β-catenin axis has an important and universal function in cancer development and progression [44,45].…”
Section: Discussionsupporting
confidence: 64%
“…3), thereby enhancing the proliferation and migration of NSCLC cells. In line with this, other groups have recently reported that CASC15 could promote tumorigenesis by activating Wnt//β-catenin signaling pathway in colon cancer and melanoma, suggesting that CASC15/β-catenin axis has an important and universal function in cancer development and progression [44,45].…”
Section: Discussionsupporting
confidence: 64%
“…Other studies have also con rmed that HULC can advance the proliferation of HCC cells and is positively related to the invasion of liver cancer cells [32]. LncRNA CASC15 has been found abnormally expressed in a variety of malignant tumors [33]. This study found that the expression level of CASC15 in HCC was increased.…”
Section: Discussionsupporting
confidence: 57%
“…In the current research, we discovered that silencing UNC5B-AS1 also repressed colon cancer HCT116 and Caco-2 cell migration and invasion, which illustrated that UNC5B-AS1 also engaged in the modulation of colon cancer metastasis and silencing UNC5B-AS1 could repress colon cancer metastasis. Moreover, in light of many other lncRNAs, such as lncRNA-activated by TGF-b (ATB) [25], lncRNA-cancer susceptibility 15 (CASC15) [26] and lncRNA-SUMO1P3 [27] also engaged in adjusting colon cancer growth and metastasis, we can put forward that colon cancer growth and metastasis are modulated by many lncRNAs that may from a very complicated regulatory network.…”
Section: Discussionmentioning
confidence: 99%